Knowledge, attitude, and practices towards rabies: A community survey in selected areas of KwaZulu-Natal Province, South Africa - Mohube Titus Letsoalo; Daniel Nenene Qekwana; Christian A. Mbajiorgu; Ishmael Festus Jaja; James Wabwire Oguttu (PLoS ONE, 2026)
Knowledge, attitude, and practices (KAP) studies have been widely used to assess gaps in KAP towards rabies. However, there is no evidence of baseline studies that have assessed KAP towards rabies among selected communities in KwaZulu-Natal Province, South Africa. A cross-sectional, questionnaire-based study design was adopted. Participants (n = 768) were selected using systematic random sampling. Data from respondents (≥18 years of age) were collected using a validated questionnaire and analysed using descriptive and inferential statistics. Overall, 26.95% (207/768) of the respondents could name the cause of rabies, while 53.52% (411/768) indicated that they would adhere to post-exposure prophylaxis (PEP), which can include, depending on the category of the bite wound, wound washing, and receiving a dose of human rabies immune globulin (HRIG) and rabies vaccine at the time of the first medical visit. Most respondents (90.10%, 692/768) would seek medical attention following a dog bite. Most dog owners (82.11%, 459/559) owned a vaccination certificate for their pet. Allowing dogs to roam without supervision was widely reported by the respondents. Dog ownership was the only factor significantly associated (p = 0.0001) with knowledge of rabies. Gaps in some aspects of knowledge about rabies were observed, which require awareness creation among residents of the study area, irrespective of whether they own pets.